If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3(-2X + 6) = -6 Reorder the terms: 10x + 3(6 + -2X) = -6 10x + (6 * 3 + -2X * 3) = -6 10x + (18 + -6X) = -6 Reorder the terms: 18 + -6X + 10x = -6 Solving 18 + -6X + 10x = -6 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -6X + -18 + 10x = -6 + -18 Reorder the terms: 18 + -18 + -6X + 10x = -6 + -18 Combine like terms: 18 + -18 = 0 0 + -6X + 10x = -6 + -18 -6X + 10x = -6 + -18 Combine like terms: -6 + -18 = -24 -6X + 10x = -24 Add '-10x' to each side of the equation. -6X + 10x + -10x = -24 + -10x Combine like terms: 10x + -10x = 0 -6X + 0 = -24 + -10x -6X = -24 + -10x Divide each side by '-6'. X = 4 + 1.666666667x Simplifying X = 4 + 1.666666667x
| M-4=16 | | 6(2x+3)=-42 | | n+5=132 | | 33=7x-2x+3 | | 4g+8=2g+2 | | -91+m=-13 | | (7-6x)/(5x+2) | | -7x+21=-7 | | M/4=50 | | 15=6x-5x+8 | | -1/4T=-2.5 | | 6(x-5)=5x-3 | | -0.12=-y/0.3 | | 0.6666666667x-0.1666666667=0.5x+0.8333333333 | | 180=103-x+6x-7 | | 2x+(9-6)=17 | | (-4+2i)-6-3= | | 3x-3(2x-5)=27 | | 5x=4y-26 | | 26-n=-73 | | 8x/-6 | | 6a^2-60a+96= | | (5x+2)/(7-6x) | | 4(3+5x)-4=28 | | 5=-2-(-1y) | | 2/3+2r=-86/15 | | -j-2(j+a)=0 | | 2x+5(x-2)=25 | | 3.2d-5-4.5d+3= | | 8.3=-4g | | 6x=12x+4 | | 5x+5=5(X-6) |